Positive electrode material precursor and preparation method thereof, lithium ion battery positive electrode material, lithium ion battery and electric equipment

By providing a positive electrode material precursor with a specific porosity and specific surface area, the chemical instability and mechanical degradability problems of high nickel positive electrode materials in lithium-ion batteries are solved, and the effect of improving the capacity and circulation performance of lithium-ion batteries is achieved.

CN119911990APending Publication Date: 2025-05-02GUANGXI CNGR NEW ENERGY SCI & TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411960211.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing high-nickel layered positive electrode materials have surface chemical instability and mechanical degradability in lithium-ion batteries, resulting in poor electrochemical reversible performance and stability and fast capacity attenuation.

Method used

A positive electrode material precursor is provided, which consists of secondary particles composed of primary particles, with a porosity of 8-20% and a specific surface area of ​​5-10 m2/g, and is prepared by a specific preparation method.

Benefits of technology

The positive electrode material precursor can reduce the sintering temperature required for the process of preparing the positive electrode material, reduce discharge capacity loss, improve safety, and improve the capacity and circulation performance of the lithium-ion battery by increasing the contact area between the positive electrode material and the electrolyte and the Li+ transmission channel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911990A_ABST
    Figure CN119911990A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and electric equipment. The positive electrode material precursor comprises secondary particles composed of primary particles, and the porosity of the secondary particles is 8-20%; the specific surface area of the positive electrode material precursor is 5-10m < 2 > / g. The specific surface area of the positive electrode material precursor provided by the invention is small, the sintering temperature required in the process of preparing the positive electrode material can be reduced, and the discharge capacity loss is reduced; the high porosity of the secondary particles in the precursor can increase the contact area between the obtained positive electrode material and an electrolyte, and increase the Li < + > transmission channel. When the positive electrode material precursor provided by the invention is applied to the lithium ion battery, the obtained lithium ion battery has high capacity and excellent cycle performance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material precursor and a preparation method thereof, a lithium-ion battery positive electrode material, a lithium-ion battery, and electrical equipment. Background Art

[0002] Lithium-ion batteries (LIBs) have the characteristics of high volume / weight energy density and long cycle life, and are widely used in the field of electric vehicles. The energy and power density of lithium-ion batteries are usually determined by the cathode material, and the structure and performance of the cathode material are inherited to a certain extent from the structure and performance of the cathode material precursor. At present, high-nickel layered cathode materials are widely used due to Ni 2+ / Ni 3+ / Ni 4+ The dual redox reaction has a high reversible capacity and has been applied to lithium-ion batteries to meet the requirements of electric vehicles and hybrid vehicles to further increase the energy density. However, with the increase of Ni content, high-nickel cathode materials will have serious surface chemical instability and mechanical degradation, resulting in poor electrochemical reversibility and stability, and rapid capacity decay.

[0003] Therefore, developing a lithium-ion cathode material precursor with a suitable internal structure is of great significance for obtaining high-performance cathode materials. Summary of the invention

[0004] The purpose of the present invention is to provide a positive electrode material precursor and a preparation method thereof, a lithium ion battery positive electrode material, a lithium ion battery and electrical equipment, aiming to solve at least one of the above-mentioned technical problems in the prior art.

[0005] In order to achieve the above object, the first aspect of the present invention provides a positive electrode material precursor, wherein the positive electrode material precursor comprises secondary particles composed of primary particles, wherein the porosity of the secondary particles is 8-20%; the specific surface area of ​​the positive electrode material precursor is 5-10m 2 / g.

[0006] Preferably, the pore uniformity coefficient R of the secondary particles is 2 ≥0.90.

[0007] Preferably, the average width of the primary particles on the surface of the positive electrode material precursor is 80-200 nm.

[0008] Preferably, the primary particles on the surface of the positive electrode material precursor are thin.

[0009] Preferably, the average aspect ratio of the primary particles on the surface of the positive electrode material precursor is (6-14):1.

[0010] Preferably, the particle size D50 of the positive electrode material precursor is 16-20 μm, and can be optionally 17-19 μm.

[0011] Preferably, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.5≤x<1, 0.01≤y≤0.20, 0.05≤z≤0.30, 0≤v≤0.015, and M is selected from at least one of Al, Ti, Zr, Mo, W, B, Mg, Ba, Nb and Sr.

[0012] According to a preferred embodiment, the cathode material precursor satisfies one or more of the following conditions:

[0013] A. The porosity of the secondary particles is 13%-16%;

[0014] B. The specific surface area of ​​the positive electrode material precursor is 6-8m 2 / g;

[0015] C. Porosity uniformity coefficient R of the secondary particles 2 ≥0.95, optionally, the pore uniformity coefficient R of the secondary particles 2 ≥0.98;

[0016] D. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.8≤x<1, 0.03≤y≤0.10, 0.05≤z≤0.30, 0≤v≤0.015, and M is selected from at least one of Al, Ti, Zr, Mo, W, B, Mg, Ba, Nb and Sr.

[0017] A second aspect of the present invention provides a method for preparing a cathode material precursor as described in the first aspect, the preparation method comprising the following steps:

[0018] mixing a precipitant solution, a complexing agent solution and water to obtain a first base solution;

[0019] Under the protection of inert gas, the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the first base liquid respectively and simultaneously to carry out a first coprecipitation reaction to obtain an intermediate;

[0020] mixing the intermediate, the precipitant solution, the complexing agent solution and water to obtain a second base solution;

[0021] The metal salt solution, the precipitant solution and the complexing agent solution are introduced into the second base solution simultaneously to carry out a second coprecipitation reaction, so as to obtain the positive electrode material precursor.

[0022] Preferably, the preparation method satisfies one or more of the following conditions:

[0023] (1) the pH value of the first base liquid is greater than the pH value of the second base liquid;

[0024] (2) the temperature of the first coprecipitation reaction is less than the temperature of the second coprecipitation reaction;

[0025] (3) controlling the flow rate of the precipitant solution so that the pH value of the first coprecipitation reaction sequentially undergoes a first descending period, a first plateau period, a second descending period, and a second plateau period;

[0026] (4) controlling the flow rate of the precipitant solution so that the second co-precipitation reaction includes a pH drop phase I and a pH plateau phase I;

[0027] (5) The average particle size of the intermediate is 3.6-5.0 μm;

[0028] (6) The sum of the molar concentrations of the metal elements in the metal salt solution is 1-3 mol / L;

[0029] (7) The precipitant solution is a sodium hydroxide solution;

[0030] (8) The complexing agent solution is an aqueous ammonia solution.

[0031] Preferably, the preparation method satisfies one or more of the following conditions:

[0032] a. The pH value of the first base liquid is 11.00-12.00, and the pH value of the second base liquid is 10.00-11.00;

[0033] b. The temperature of the first coprecipitation reaction is 50-60°C, and the temperature of the second coprecipitation reaction is 65-80°C;

[0034] c. the concentration of the complexing agent in the first base solution and the concentration of the complexing agent in the first coprecipitation reaction are each independently 3.0-5.0 g / L;

[0035] d. the concentration of the complexing agent in the second base solution and the concentration of the complexing agent in the second coprecipitation reaction are each independently 3.0-5.0 g / L;

[0036] e. The pH value of the first plateau in the first coprecipitation reaction is 10.50-11.00;

[0037] f. The first coprecipitation reaction in the first plateau period is maintained for 6-10h;

[0038] g. The pH value of the second plateau in the first coprecipitation reaction is 10.00-10.50;

[0039] h. The second coprecipitation reaction further comprises a pH drop phase II, a pH plateau phase II, a pH drop phase III, a pH plateau phase III, and the pH value of the pH plateau phase III in the second coprecipitation reaction is 9.60-10.00;

[0040] h. The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.60-10.00.

[0041] A third aspect of the present invention provides a positive electrode material for a lithium ion battery, wherein the raw material of the positive electrode material for a lithium ion battery includes the positive electrode material precursor as described in the first aspect.

[0042] A fourth aspect of the present invention provides a lithium ion battery, comprising the lithium ion battery positive electrode material as described in the third aspect.

[0043] A fifth aspect of the present invention provides an electrical device, comprising the lithium-ion battery as described in the fourth aspect.

[0044] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:

[0045] The cathode material precursor provided by the present invention has a small specific surface area (5-10m 2 / g), which can reduce the sintering temperature required for the preparation of positive electrode materials, reduce discharge capacity loss, and improve safety; the high porosity (8-20%) of the secondary particles in the precursor can increase the contact area between the obtained positive electrode material and the electrolyte, increasing Li + Transmission channel. The positive electrode material precursor provided by the present invention is applied to a lithium-ion battery, and the obtained lithium-ion battery has both high capacity and excellent cycle performance.

[0046] The preparation method of the positive electrode material precursor provided by the present invention is simple, highly operable, and is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is a SEM image of the cathode material precursor provided in Example 1 of the present invention;

[0048] Figure 2 is a CP diagram of the cathode material precursor provided in Example 1 of the present invention;

[0049] Figure 3 is a SEM image of the cathode material precursor provided in Example 2 of the present invention;

[0050] Figure 4 is a CP diagram of the cathode material precursor provided in Example 2 of the present invention;

[0051] Figure 5 is a SEM image of the cathode material precursor provided in Example 3 of the present invention;

[0052] Figure 6 is a CP diagram of the cathode material precursor provided in Example 3 of the present invention;

[0053] Figure 7 is a SEM image of the cathode material precursor provided in Example 4 of the present invention;

[0054] Figure 8 is a CP diagram of the cathode material precursor provided by Example 4 of the present invention;

[0055] Fig. 9 is a SEM image of the cathode material precursor provided in Example 5 of the present invention;

[0056] Fig.10 is a CP diagram of the cathode material precursor provided in Example 5 of the present invention;

[0057] Fig.11 is a SEM image of the cathode material precursor provided in Example 6 of the present invention;

[0058] Fig.12 is a CP diagram of the cathode material precursor provided by Example 6 of the present invention;

[0059] Fig.13 is a SEM image of the positive electrode material precursor provided in Comparative Example 1 of the present invention;

[0060] Fig.14 It is a CP diagram of the positive electrode material precursor provided in Comparative Example 1 of the present invention;

[0061] Fig.15 is a SEM image of the positive electrode material precursor provided in Comparative Example 2 of the present invention;

[0062] Fig.16 It is a CP diagram of the positive electrode material precursor provided in Comparative Example 2 of the present invention;

[0063] Fig.17 is a SEM image of the positive electrode material precursor provided in Comparative Example 3 of the present invention;

[0064] Fig.18 It is a CP diagram of the positive electrode material precursor provided in Comparative Example 3 of the present invention;

[0065] Fig.19 It is a schematic diagram of the division of the pore uniformity coefficient calculation area in Example 5 of the present invention. DETAILED DESCRIPTION

[0066] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0067] It should be noted that, in various aspects of the present invention, for the same components or terms in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.

[0068] As used herein:

[0069] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0070] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0071] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0072] In these examples, parts and percentages are by mass unless otherwise indicated.

[0073] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0074] "And / or" is used to indicate that one or both of the situations described may occur, for example, A and / or B includes (A and B) and (A or B). It should be clarified that the descriptions such as "thin" in the present invention specifically refer to the morphological characteristics of the corresponding structure in the positive electrode material precursor and cannot be understood as specific quantification.

[0075] In the present invention, the morphology of the cathode material precursor is characterized by a scanning electron microscope (SEM); the internal structure of the cathode material precursor is characterized by ion beam milling (CP) and a scanning electron microscope.

[0076] In the present invention, the particle size D50 and the average particle size have the same meaning, and refer to the particle size corresponding to when the cumulative particle size distribution percentage of the positive electrode material precursor reaches 50%.

[0077] The cross section of a sphere refers to a plane figure obtained by cutting a sphere with a plane. In the present invention, unless otherwise specified, the secondary particle cross section and the secondary particle profile have the same meaning, which refers to a plane figure formed by the cutting plane passing through the center of the sphere or the center of the particle.

[0078] In the present invention, the porosity of the secondary particles refers to the internal porosity of the secondary particles, which is measured by porosity statistical software.

[0079] The porosity testing method is: use image analysis software (ImageJ) to directly calculate the pore area and cross-sectional area of ​​the CP profile, and calculate the porosity of different areas by "internal porosity = secondary particle internal cross-sectional pore area / secondary particle cross-sectional area × 100%". The porosity in this article is characterized by this method.

[0080] In the present invention, the pore uniformity coefficient R 2 , which is used to indicate the uniformity of pore distribution. The specific calculation steps are as follows:

[0081] Step 1: Treat a single cathode material precursor secondary particle as a sphere, calculate based on the cross section of the sphere, and fit the cross section into a regular circle according to the equal area rule to determine the center of the circle. Starting from the center of the circle, draw n (n≥3) concentric circles radially to divide the circle into n+1 parts. For details, see the attached Fig.19 , where n = 4, and is divided into 5 parts, which are the circles surrounded by the ring A (area is S A ), the area between ring A and ring B (area S AB ), the area between the ring B and the ring C (area is S BC ), the area between the ring C and the ring D (area is S CD ), and the area outside the ring D (area is S D );

[0082] Step 2: Calculate the area x of each part and the pore area y of the corresponding area;

[0083] Step 3: According to the principle of least squares method, establish the linear relationship between x and y and calculate the correlation coefficient R 2 , where the correlation coefficient R 2 The calculation method is:

[0084] When R 2 When ≥0.9, the pore distribution is considered uniform. 2 When R is between 0.9 and 0.95, the pore distribution is considered to be relatively uniform. 2 When R 2 When <0.9, it is considered that the pore distribution is not uniform enough.

[0085] In the present invention, unless otherwise specified, the calculation method of the average length, average width and average aspect ratio of the primary particles on the surface of the positive electrode material precursor is as follows: 1) obtaining the length and width of a single primary particle on the surface of the positive electrode material precursor, the testing method is as follows: 1) randomly selecting 5 secondary particles with a particle size in the range of D50±2μm, and randomly selecting 10 primary particles from the surface of each secondary particle, and obtaining a total of 50 primary particles, 2) using Nano Measurer software to measure the length and width of the 50 primary particles in the SEM image with a magnification of 10000-100000 times, and respectively calculating the average length and average width, wherein the longest axis of a single primary particle is regarded as its length, and the short axis measured perpendicular to the midpoint of the longest axis is regarded as its width, 3) calculating the ratio of the average length to the average width, which is the average aspect ratio of the primary particles on the surface of the positive electrode material precursor.

[0086] As mentioned above, the first aspect of the present invention provides a positive electrode material precursor, wherein the positive electrode material precursor comprises secondary particles composed of primary particles, wherein the porosity of the secondary particles is 8-20%; the specific surface area of ​​the positive electrode material precursor is 5-10m 2 / g.

[0087] In some embodiments, the porosity of the secondary particles is 13%-16%, for example, 13%, 14%, 15%, 16% or any value between 13% and 16%.

[0088] In some embodiments, the specific surface area of ​​the cathode material precursor is 6-8 m 2 / g, for example, 6m 2 / g, 7m 2 / g, 8m 2 / g or 6-8m 2 Any value between / g.

[0089] In the present invention, by controlling the porosity of the secondary particles in the positive electrode material precursor and the specific surface area of ​​the positive electrode material precursor within the above range, the obtained positive electrode material precursor is applied to the positive electrode material of a lithium ion battery, so that the overall capacity and cycle performance of the positive electrode material are better.

[0090] In some embodiments, the pore uniformity coefficient R of the secondary particles is 2 ≥0.90.

[0091] In some embodiments, the pore uniformity coefficient R of the secondary particles is 2 ≥0.92, preferably, the pore uniformity coefficient R of the secondary particles 2 ≥0.95, further preferably, the pore uniformity coefficient R of the secondary particles 2 ≥0.98.

[0092] In some embodiments of the present invention, the pore uniformity coefficient R of the secondary particles in the positive electrode material precursor is 2 High and evenly distributed pores can shorten the transmission path of lithium ions, increase the lithium ion diffusion rate, and improve the rate performance.

[0093] In some embodiments, the primary particles on the surface of the positive electrode material precursor are thin.

[0094] In some embodiments, the average aspect ratio of the primary particles in the surface of the positive electrode material precursor is (6-14):1. For example, the average aspect ratio of the primary particles in the surface of the positive electrode material precursor can be 6:1, 7:1, 10:1, 12:1, 14:1 or any value between (6-14):1. In the present invention, it can be optionally (8-10):1.

[0095] In some embodiments of the present invention, the thin primary particles (average aspect ratio is (6-14): 1) on the surface of the positive electrode material precursor correspond to thin and short primary particles of the positive electrode material, which can shorten the diffusion path of lithium ions, facilitate the deintercalation of lithium ions in the positive electrode material, and thus improve the first efficiency (referring to the percentage of battery capacity efficiency during the first charge and discharge process of the battery).

[0096] In some embodiments, the average length of the primary particles on the surface of the positive electrode material precursor is 800-1200 nm, for example, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm or any value between 800-1200 nm.

[0097] In some embodiments, the average width of the primary particles on the surface of the positive electrode material precursor is 80-200 nm, for example, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm or any value between 80-200 nm.

[0098] In some embodiments of the present invention, the primary particles of the positive electrode material precursor are arranged radially, which can reduce the intercrystalline stress during the cycle, improve the stability of the material during the cycle, and construct a direct diffusion path for lithium ions inside the secondary particles, so that the positive electrode material has a high capacity retention rate and excellent cycle performance.

[0099] In some embodiments, the tap density of the cathode material precursor is 1.60-2.00 g / cm 3 , for example, it can be 1.60 g / cm 3 , 1.70g / cm 3 , 1.80g / cm 3 , 1.90g / cm 3 , 2.00g / cm 3 or 1.60-2.00g / cm 3 Any value in between.

[0100] In some embodiments, the particle size D50 of the positive electrode material precursor is 16-20 μm, for example, the particle size D50 may be 16 μm, 18 μm, 20 μm or any value between 16-20 μm;

[0101] Optionally, the particle size D50 of the positive electrode material precursor is 17-19 μm.

[0102] In some embodiments, the chemical formula of the cathode material precursor is Ni x Co y Mn z M v(OH)2, wherein x+y+z+v=1, 0.5≤x<1, 0.01≤y≤0.20, 0.05≤z≤0.30, 0≤v≤0.015, M is selected from at least one of Al, Ti, Zr, Mo, W, B, Mg, Ba, Nb and Sr;

[0103] Optionally, 0.8≤x<1, 0.03≤y≤0.10.

[0104] In some embodiments, the sphericity of the cathode material precursor is 90%-99%, preferably 94%-97%.

[0105] As mentioned above, the second aspect of the present invention provides a method for preparing a positive electrode material precursor as described in the first aspect, the preparation method comprising the following steps:

[0106] mixing a precipitant solution, a complexing agent solution and water to obtain a first base solution;

[0107] Under the protection of inert gas, the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the first base liquid respectively and simultaneously to carry out a first coprecipitation reaction to obtain an intermediate;

[0108] mixing the intermediate, the precipitant solution, the complexing agent solution and water to obtain a second base solution;

[0109] The metal salt solution, the precipitant solution and the complexing agent solution are introduced into the second base solution simultaneously to carry out a second coprecipitation reaction, so as to obtain the positive electrode material precursor.

[0110] In some embodiments, the coprecipitation reaction is carried out in a reactor, and when the upper limit of the reactor volume is reached, concentration is started to allow the reactor to be used continuously.

[0111] The present invention has no special requirements for the concentration conditions, and those skilled in the art can select them as needed.

[0112] The present invention has no special requirements on the type of water, and those skilled in the art can select it as needed. Exemplarily, the water is pure water.

[0113] The present invention has no special requirements on the type of the inert gas, and those skilled in the art can select it as needed. Exemplarily, the inert gas is nitrogen.

[0114] According to a preferred specific embodiment, the preparation method further comprises: after performing the first coprecipitation reaction, dehydrating the product of the first coprecipitation reaction to obtain the intermediate, and the intermediate is used as the crystal nucleus of the second coprecipitation reaction for continuing the growth reaction.

[0115] The present invention has no special requirements on the conditions of the dehydration treatment. It is only necessary to dry the product of the first coprecipitation reaction. Those skilled in the art can select the conditions according to means known in the art.

[0116] In some embodiments, the pH value of the first base liquid is greater than the pH value of the second base liquid.

[0117] In some embodiments, the temperature of the first coprecipitation reaction is less than the temperature of the second coprecipitation reaction.

[0118] In some embodiments, the flow rate of the precipitant solution is controlled so that the pH value of the first co-precipitation reaction sequentially undergoes a first decline period, a first plateau period, a second decline period, and a second plateau period.

[0119] In some embodiments, the pH value of the first plateau phase in the first coprecipitation reaction is 10.50-11.00, for example, it can be any value between 10.50-10.60, 10.60-10.70, 10.70-10.80, 10.90-11.00 or 10.00-11.001. Preferably, the pH value of the first plateau phase in the first coprecipitation reaction is 10.50-10.70.

[0120] In some embodiments, the first plateau phase in the first coprecipitation reaction is maintained for 6-10 h, for example, 6 h, 7 h, 8 h, 9 h, 10 h or any value between 6-10 h.

[0121] In some embodiments, the pH value of the second plateau in the first coprecipitation reaction is 10.00-10.50, for example, it can be any value between 10.00-10.10, 10.10-10.20, 10.20-10.30, 10.30-10.40, 10.40-10.50 or 10.00-10.50. Preferably, the pH value of the second plateau in the first coprecipitation reaction is 10.15-10.30.

[0122] In some embodiments, the pH value reduction rate in the first decline period and the pH value reduction rate in the second decline period in the first co-precipitation reaction are each independently 0.1-0.2 / h, for example, 0.1 / h, 0.2 / h or any value between 0.1-0.2 / h.

[0123] In some embodiments, the flow rate of the precipitant solution is controlled so that the pH value of the second co-precipitation reaction sequentially undergoes a pH drop period I and a pH plateau period I.

[0124] In some embodiments, the pH value of the pH plateau phase I in the second coprecipitation reaction is 9.60-10.10, for example, it can be 9.60-9.70, 9.70-9.80, 9.80-9.90, 9.90-10.00, 10.00-10.10 or any value between 9.60-10.10.

[0125] In some embodiments, the pH value of the second co-precipitation reaction sequentially undergoes pH decline period I, pH plateau period I, pH decline period II, pH plateau period II, pH decline period III, and pH plateau period III, and the pH value of the pH plateau period III is 9.60-10.00, for example, it can be any value between 9.60-9.70, 9.70-9.80, 9.80-9.90, 9.90-10.00 or 9.60-10.00. Optionally, the pH value of the pH plateau period III is 9.60-9.80.

[0126] In some embodiments, the average particle size of the intermediate is 3.6-5.0 μm, for example, 3.6 μm, 3.8 μm, 4.0 μm, 4.5 μm, 5.0 μm or any value between 3.6-5.0 μm.

[0127] In some embodiments, the sum of the molar concentrations of the metal elements in the metal salt solution is 1-3 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L or any value between 1-3 mol / L.

[0128] In some embodiments, the precipitant solution is a sodium hydroxide solution.

[0129] In some embodiments, the concentration of the precipitant solution is 5-10 mol / L, for example, it can be 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L or any value between 5-10 mol / L.

[0130] In some embodiments, the complexing agent solution is an aqueous ammonia solution.

[0131] In some embodiments, the concentration of the complexing agent solution is 10-15 mol / L, for example, it can be 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L, 15 mol / L or any value between 10-15 mol / L.

[0132] In some embodiments, the pH value of the first base liquid is 11.00-12.00, for example, it can be 11.00-11.10, 11.10-11.20, 11.20-11.30, 11.30-11.40, 11.40-11.50, 11.50-11.60, 11.60-11.70, 11.70-11.80, 11.90-12.00 or any value between 11.00-12.00, preferably, the pH value of the first base liquid is 11.10-11.50, more preferably, the pH value of the first base liquid is 11.20-11.40.

[0133] In some embodiments, the pH value of the second base liquid is 10.00-11.00, for example, it can be 10.00-10.10, 10.10-10.20, 10.20-10.30, 10.30-10.40, 10.40-10.50, 10.50-10.60, 10.60-10.70, 10.70-10.80, 10.90-11.00 or any value between 10.00-11.00, preferably, the pH value of the second base liquid is 10.10-10.50, more preferably, the pH value of the second base liquid is 10.20-10.40, and further preferably, the pH value of the second base liquid is 10.25-10.35.

[0134] In some embodiments, the temperature of the first coprecipitation reaction is 50-60°C, for example, 50°C, 55°C, 60°C or any value between 50-60°C; the temperature of the second coprecipitation reaction is 65-80°C, for example, 65°C, 70°C, 80°C or any value between 65-80°C.

[0135] In some embodiments, the concentration of the complexing agent in the first base solution and the concentration of the complexing agent in the first coprecipitation reaction are each independently 3.0-5.0 g / L, for example, 3.0-3.5 g / L, 3.0-4.0 g / L, 3.5-4.0 g / L, 4.0-4.5 g / L, 4.5-5.0 g / L or any value between 3.0-5.0 g / L.

[0136] In some embodiments, the concentration of the complexing agent in the second base solution and the concentration of the complexing agent in the second coprecipitation reaction are each independently 3.0-5.0 g / L, for example, 3.0-3.5 g / L, 3.0-4.0 g / L, 3.5-4.0 g / L, 4.0-4.5 g / L, 4.5-5.0 g / L or any value between 3.0-5.0 g / L.

[0137] The preparation method of the positive electrode material precursor of the present invention may also include post-processing means known in the art such as washing, centrifugation, drying, screening, and demagnetization, so as to obtain the positive electrode material precursor with better quality. The present invention will not be repeated here, and those skilled in the art should not understand it as a limitation of the present invention.

[0138] As mentioned above, the third aspect of the present invention provides a positive electrode material for a lithium-ion battery, wherein the raw material of the positive electrode material for a lithium-ion battery includes the positive electrode material precursor as described in the first aspect.

[0139] The present invention has no particular limitation on the method for preparing a positive electrode material for a lithium ion battery using the positive electrode material precursor provided by the present invention, and those skilled in the art can select the method according to the technical means known in the art. However, in order to obtain a positive electrode material for a lithium ion battery with better electrochemical performance, the present invention preferably uses the following method to prepare the positive electrode material for a lithium ion battery.

[0140] According to a preferred specific embodiment, the method for preparing the positive electrode material of a lithium ion battery comprises:

[0141] Evenly mixing the positive electrode material precursor and the lithium-containing compound to obtain a mixed material;

[0142] The mixed material is sintered under air atmosphere to obtain the positive electrode material for lithium-ion battery.

[0143] The preparation method of the lithium ion battery positive electrode material of the present invention may also include cooling, crushing, screening and other post-processing means known in the art to obtain the lithium ion battery positive electrode material with better quality. The present invention will not be repeated here, and those skilled in the art should not be understood as limiting the present invention.

[0144] In some embodiments, the lithium-containing compound is Li2CO3 and / or LiOH.

[0145] In some embodiments, the sintering conditions include: a temperature of 700-800°C, for example, 700, 740, 780°C, 800°C or any value between 700-800°C; a sintering time of 10-15h, for example, 10h, 11h, 12h, 13h, 14h, 15h or any value between 10-15h.

[0146] In some embodiments, the molar ratio of the positive electrode material precursor to the lithium-containing compound is 1:1.01-1.05.

[0147] As mentioned above, the fourth aspect of the present invention provides a lithium-ion battery, comprising the lithium-ion battery positive electrode material as described in the third aspect.

[0148] As mentioned above, the fifth aspect of the present invention provides an electrical device, including the lithium-ion battery as described in the fourth aspect.

[0149] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0150] Diaphragm: The model is PE double-layer ceramic diaphragm.

[0151] Electrolyte: ethylene carbonate solution containing lithium hexafluorophosphate (the concentration of lithium hexafluorophosphate is 1 mol / L): dimethyl carbonate (DMC), volume ratio = 1:1.

[0152] Example 1

[0153] Prepare a chemical formula Ni 0.94 Co 0.05 Mn 0.01 (OH)2, a cathode material precursor with a particle size D50 of 17.5 μm, and a specific preparation method thereof is as follows:

[0154] ①Raw material preparation:

[0155] Prepare a metal salt solution: mix nickel sulfate crystals, cobalt sulfate crystals, manganese sulfate crystals and pure water to obtain a metal salt solution, wherein the molar ratio of Ni:Co:Mn in the metal salt solution is controlled to be 94:5:1, and the sum of the molar concentrations of the metal elements in the metal salt solution is 2 mol / L;

[0156] Prepare a precipitant solution: dissolve sodium hydroxide in water to prepare a 10 mol / L sodium hydroxide solution;

[0157] Prepare complexing agent solution: prepare ammonia solution with a concentration of 12 mol / L as complexing agent solution;

[0158] Prepare the first primer:

[0159] In a reaction kettle, a sodium hydroxide solution, an ammonia solution and pure water are mixed to obtain a first bottom liquid, the pH of the first bottom liquid is controlled to be 11.20-11.40, and the mass concentration of the ammonia solution in the first bottom liquid is 3.0-4.0 g / L;

[0160] ②First coprecipitation reaction

[0161] Under nitrogen protection, a metal salt solution (with a flow rate of 1% / h of the volume of the reactor), a precipitant solution (with a flow rate of 0.39% / h of the volume of the reactor) and a complexing agent solution (with a flow rate of 0.03% / h of the volume of the reactor) are respectively introduced into the first base liquid to carry out a first coprecipitation reaction (the mother liquor is discharged through a concentration device during the reaction, and the discharge rate is consistent with the total feed amount), and the product of the first coprecipitation reaction is dehydrated to obtain an intermediate with a particle size D50 of 3.8 μm;

[0162] Controlling the flow rate of the precipitant solution so that the pH value of the first coprecipitation reaction sequentially experiences a first descending period, a first plateau period, a second descending period, and a second plateau period;

[0163] The time of the first decline phase in the first coprecipitation reaction was 5 h (the rate of decrease of the pH value fluctuated between 0.1-0.2 / h);

[0164] The pH value of the first plateau in the first coprecipitation reaction was 10.7, and the maintenance time was 7 h;

[0165] The pH value of the second plateau in the first coprecipitation reaction was 10.15;

[0166] The temperature of the first coprecipitation reaction was 55°C;

[0167] The mass concentration of ammonia water in the first coprecipitation reaction is 3.0-4.0 g / L;

[0168] ③Prepare the second base liquid:

[0169] Mixing the intermediate, the precipitant solution, the complexing agent solution and pure water to obtain a second base solution; controlling the pH of the second base solution to be 10.25-10.35, and the mass concentration of ammonia water in the second base solution to be 3.0-4.0 g / L;

[0170] ④Second coprecipitation reaction

[0171] The metal salt solution (the flow rate is 2-8% / h of the volume of the reactor, and the flow rate is increased every 4 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow rate ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 17.5 μm is obtained;

[0172] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a pH drop period I and a pH plateau period I;

[0173] The time of pH decline phase I in the second coprecipitation reaction was 3 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0174] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.95-10.10;

[0175] The temperature of the second coprecipitation reaction was 75°C;

[0176] The mass concentration of ammonia water in the second coprecipitation reaction is 3.0-4.0 g / L;

[0177] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Figure 1 As shown in the CP diagram, Figure 2 shown).

[0178] The positive electrode material precursor has a sphericity of 95.02% and a tap density of 1.9 g / cm3.

[0179] Example 2

[0180] Prepare a chemical formula Ni 0.85 Co 0.10 Mn 0.05 (OH)2, cathode material precursor with particle size D50 of 18 μm:

[0181] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:

[0182] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 85:10:5;

[0183] In step ③, the mass concentration of ammonia water in the second base liquid is 3.5-4.0 g / L;

[0184] In step ④, the metal salt solution (the flow rate is 2-10% / h of the volume of the reactor, and the flow rate is increased every 4 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through a concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 18 μm is obtained;

[0185] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a pH drop period I and a pH plateau period I;

[0186] The time of pH decline phase I in the second coprecipitation reaction was 3 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0187] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.80-10.00;

[0188] The temperature of the second coprecipitation reaction was 75°C;

[0189] The mass concentration of ammonia water in the second coprecipitation reaction is 3.5-4.0 g / L;

[0190] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Figure 3 As shown in the CP diagram, Figure 4 shown);

[0191] The unlisted parts are the same as those in Example 1.

[0192] The positive electrode material precursor has a sphericity of 96.32% and a tap density of 1.74 g / cm3.

[0193] Example 3

[0194] Prepare a chemical formula Ni 0.90 Co 0.06 Mn 0.04 (OH)2, cathode material precursor with particle size D50 of 20 μm:

[0195] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:

[0196] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 90:6:4;

[0197] In step ③, the mass concentration of ammonia water in the second base liquid is 4.0-5.0 g / L;

[0198] In step ④, the metal salt solution (the flow rate is 2-12% / h of the volume of the reactor, and the flow rate is increased every 3 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through a concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 20 μm is obtained;

[0199] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a pH drop period I and a pH plateau period I;

[0200] The time of pH decline phase I in the second coprecipitation reaction was 3 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0201] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.80-10.00;

[0202] The temperature of the second coprecipitation reaction is 80°C;

[0203] The mass concentration of ammonia water in the second coprecipitation reaction is 4.0-5.0 g / L;

[0204] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Figure 5 As shown in the CP diagram, Figure 6 shown);

[0205] The unlisted parts are the same as those in Example 1.

[0206] The positive electrode material precursor has a sphericity of 95.94% and a tap density of 1.86 g / cm3.

[0207] Example 4

[0208] Prepare a chemical formula Ni 0.90 Co 0.05 Mn 0.05 (OH)2, cathode material precursor with particle size D50 of 20 μm:

[0209] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:

[0210] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 90:5:5;

[0211] In step ④, the metal salt solution (the flow rate is 2-10% / h of the volume of the reactor, and the flow rate is increased every 3 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 20 μm is obtained;

[0212] The flow rate of the precipitant solution is controlled so that the pH value of the second coprecipitation reaction sequentially undergoes pH falling period I, pH plateau period I, pH falling period II, pH plateau period II, pH falling period III, and pH plateau period III.

[0213] The time of pH decline phase I in the second coprecipitation reaction was 3 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0214] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.80-10.00, and the maintenance time is 11 hours;

[0215] The pH value decrease rate in the pH decrease period II in the second coprecipitation reaction fluctuates between 0.1-0.2 / h;

[0216] The pH value of the pH plateau phase II in the second coprecipitation reaction is 0.1 lower than the pH value of the pH plateau phase I, and the maintenance time is 9 hours;

[0217] The pH value decrease rate in the pH decrease period III in the second coprecipitation reaction fluctuates between 0.1-0.2 / h;

[0218] The pH value of the pH plateau phase III in the second coprecipitation reaction is 0.15 lower than the pH value of the pH plateau phase II (maintained between 9.60-9.80);

[0219] The temperature of the second coprecipitation reaction is 80°C;

[0220] The mass concentration of ammonia water in the second coprecipitation reaction is 3.0-4.0 g / L;

[0221] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Figure 7 As shown in the CP diagram, Figure 8 shown);

[0222] The unlisted parts are the same as those in Example 1.

[0223] The positive electrode material precursor has a sphericity of 96.54% and a tap density of 1.79 g / cm3.

[0224] Example 5

[0225] Prepare a chemical formula Ni 0.83 Co 0.05 Mn 0.12 (OH)2, cathode material precursor with particle size D50 of 19 μm:

[0226] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:

[0227] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 83:5:12;

[0228] In step ③, the mass concentration of ammonia water in the second base liquid is 3.75-4.25 g / L;

[0229] In step ④, the metal salt solution (the flow rate is 2-10% / h of the volume of the reactor, and the flow rate is increased every 3 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 19 μm is obtained;

[0230] The flow rate of the precipitant solution is controlled so that the pH value of the second coprecipitation reaction sequentially undergoes pH falling period I, pH plateau period I, pH falling period II, pH plateau period II, pH falling period III, and pH plateau period III.

[0231] The time of pH decline phase I in the second coprecipitation reaction was 3 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0232] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.80-10.00, and the maintenance time is 11 hours;

[0233] The pH value decrease rate in the pH decrease period II in the second coprecipitation reaction fluctuates between 0.1-0.2 / h;

[0234] The pH value of the pH plateau phase II in the second coprecipitation reaction is 0.1 lower than the pH value of the pH plateau phase I, and the maintenance time is 9 hours;

[0235] The pH value decrease rate in the pH decrease period III in the second coprecipitation reaction fluctuates between 0.1-0.2 / h;

[0236] The pH value of the pH plateau phase III in the second coprecipitation reaction is 0.15 lower than the pH value of the pH plateau phase II (maintained between 9.60-9.80);

[0237] The temperature of the second coprecipitation reaction was 77°C;

[0238] The mass concentration of ammonia water in the second coprecipitation reaction is 3.75-4.25 g / L;

[0239] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Fig. 9 As shown in the CP diagram, Fig.10 shown);

[0240] The unlisted parts are the same as those in Example 1.

[0241] The positive electrode material precursor has a sphericity of 95.32% and a tap density of 1.89 g / cm3.

[0242] Example 6

[0243] Prepare a chemical formula Ni 0.75 Co 0.10 Mn 0.15 (OH)2, cathode material precursor with particle size D50 of 17.5 μm:

[0244] This embodiment is carried out in a similar manner to that of Embodiment 1, except that:

[0245] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 75:10:15;

[0246] In step ③, the pH of the second base liquid is 10.15-10.25, and the mass concentration of ammonia water in the second base liquid is 3.0-4.0 g / L;

[0247] In step ④, the metal salt solution (the flow rate is 2-8% / h of the volume of the reactor, and the flow rate is increased every 3 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 17.5 μm is obtained;

[0248] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a pH drop period I and a pH plateau period I;

[0249] The time of pH decline phase I in the second coprecipitation reaction was 6 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0250] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.65-9.8;

[0251] The temperature of the second coprecipitation reaction was 65°C;

[0252] The mass concentration of ammonia water in the second coprecipitation reaction is 3.0-4.0 g / L;

[0253] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Fig.11 As shown in the CP diagram, Fig.12 shown);

[0254] The unlisted parts are the same as those in Example 1.

[0255] The positive electrode material precursor has a sphericity of 94.88% and a tap density of 1.94 g / cm3.

[0256] Comparative Example 1

[0257] Prepare a chemical formula Ni 0.88 Co 0.09 Mn 0.03 (OH)2, cathode material precursor with particle size D50 of 17.5 μm:

[0258] This comparative example was carried out in a similar manner to Example 1, except that:

[0259] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 88:9:3;

[0260] In step ③, the pH of the second base liquid is 10.55-10.65, and the mass concentration of ammonia water in the second base liquid is 4.8-5.6 g / L;

[0261] In step ④, the metal salt solution (the flow rate is 2-7.5% / h of the volume of the reactor, and the flow rate is increased every 2 hours at a rate of 1.5% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 17.5 μm is obtained;

[0262] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a rising phase and a plateau phase;

[0263] The duration of the rising phase in the second coprecipitation reaction was 2 h (the rate of increase of the pH value fluctuated between 0.1 and 0.2 / h);

[0264] The pH value of the plateau phase in the second coprecipitation reaction is 10.65-10.80;

[0265] The temperature of the second coprecipitation reaction was 55°C;

[0266] The mass concentration of ammonia water in the second coprecipitation reaction is 4.8-5.6 g / L;

[0267] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Fig.13 As shown in the CP diagram, Fig.14 shown);

[0268] The unlisted parts are the same as those in Example 1.

[0269] Comparative Example 2

[0270] Prepare a chemical formula Ni 0.83 Co 0.05 Mn 0.12 (OH)2, cathode material precursor with particle size D50 of 18 μm:

[0271] This comparative example was carried out in a similar manner to Example 1, except that:

[0272] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 83:5:12;

[0273] In step ③, the pH of the second base liquid is 10.45-10.55, and the mass concentration of ammonia water in the second base liquid is 6.5-7.5 g / L;

[0274] In step ④, the metal salt solution (the flow rate is 2-8% / h of the volume of the reactor, and the flow rate is increased every 5 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through a concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 18 μm is obtained;

[0275] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially experiences a pH drop period I and a pH plateau period I;

[0276] The time of pH decline phase I in the second coprecipitation reaction was 5 h (the rate of decrease of pH value fluctuated between 0.1-0.2 / h);

[0277] The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.80-10.00;

[0278] The temperature of the second coprecipitation reaction was 77°C;

[0279] The mass concentration of ammonia water in the second coprecipitation reaction is 6.5-7.5 g / L;

[0280] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Fig.15 As shown in the CP diagram, Fig.16 shown);

[0281] The unlisted parts are the same as those in Example 1.

[0282] Comparative Example 3

[0283] Prepare a chemical formula Ni 0.83 Co 0.05 Mn 0.12 (OH)2, cathode material precursor with particle size D50 of 18 μm:

[0284] This comparative example was carried out in a similar manner to Example 1, except that:

[0285] In step ①, the molar ratio of Ni:Co:Mn in the metal salt solution is 83:5:12;

[0286] In step ③, the pH of the second base liquid is 10.65-10.75, and the mass concentration of ammonia water in the second base liquid is 6.5-7.5 g / L;

[0287] In step ④, the metal salt solution (the flow rate is 1-6% / h of the volume of the reactor, and the flow rate is increased every 3 hours at a rate of 2% / h), the precipitant solution and the complexing agent solution (the flow ratio of the metal salt solution, the precipitant solution and the complexing agent solution is 1:0.4:0.03) are respectively introduced into the second base liquid to carry out a second coprecipitation reaction (the mother liquor is discharged through the concentration device during the reaction, and the discharge rate is consistent with the total feed amount) until a precipitate with a D50 of 18 μm is obtained;

[0288] Controlling the flow rate of the precipitant solution so that the pH value of the second coprecipitation reaction sequentially undergoes a pH drop period I, a pH plateau period I, a pH drop period II, and a pH plateau period II;

[0289] The time of pH decline phase I in the second coprecipitation reaction was 11 h (the rate of decrease of pH value fluctuated between 0.02-0.05 / h);

[0290] The pH value of the pH plateau phase I in the second coprecipitation reaction is 10.35-10.45, and the maintenance time is 20 hours;

[0291] The pH value decrease rate in the pH decrease period II in the second coprecipitation reaction fluctuates between 0.1-0.2 / h;

[0292] The pH value of the pH plateau phase II in the second coprecipitation reaction is 0.1 lower than the pH value of the pH plateau phase I;

[0293] The temperature of the second coprecipitation reaction was 47°C;

[0294] The mass concentration of ammonia water in the second coprecipitation reaction is 6.5-7.5 g / L;

[0295] ⑤ Post-treatment: The precipitate is washed, centrifuged, dried, sieved, and demagnetized in sequence to obtain a positive electrode material precursor (the SEM image of which is shown in FIG. Fig.17 As shown in the CP diagram, Fig.18 shown);

[0296] The unlisted parts are the same as those in Example 1.

[0297] Test Example 1

[0298] The positive electrode material precursor prepared in the above example was subjected to physical and chemical data testing, and the test results are shown in Table 2; specifically:

[0299] 1. Particle size D50 is tested by Malvern 3000 laser particle size analyzer, with reference to standard GB / T 19077-2016;

[0300] 2. Specific surface area (BET) is determined according to GB / T 19587-2017 gas adsorption BET method for solid matter determination;

[0301] 3. The test reference standard for tap density (TD) is GB / T 5162-2021 Determination of tap density of metal powder.

[0302] 4. The test method of sphericity is: take a SEM picture under HITACHISU8100, and then use the sphericity analysis software Avizo to intelligently identify all the positive electrode material precursor particles in the SEM image, and calculate it through the calculation formula: sphericity = (4π×area) / (circumference×circumference)×100%. It is an indicator of the roundness of the contour shape of the secondary particles. The closer the shape is to a circle, the closer it is to 100%. Several (such as 5) SEM pictures can be taken to calculate the sphericity, and then the average value is taken. The sphericity in this article is obtained by this method.

[0303] 5. Porosity uniformity coefficient R 2 Test method: Taking the positive electrode material precursor obtained in Example 5 as an example, according to Fig.10 The cross-sectional view of the image J grayscale analysis method is used to calculate the area and pore area of ​​different regions. The schematic diagram of regional segmentation is shown in Fig.19 As shown, the pore distribution uniformity verification data of the positive electrode material precursor of Example 5 is shown in Table 1. The test methods of the pore uniformity coefficient R2 of other embodiments are calculated using the same principle except that the area division is slightly different.

[0304] Table 1 Pore uniformity coefficient R of Example 5 2 Regional division and related calculation data

[0305] area <![CDATA[Area of region (μm 2 )]]> <![CDATA[Area of regional void (μm 2 )]]> Regional porosity A enclosed area <![CDATA[S A =14.795]]> 2.232 15.09% The area between AB <![CDATA[S AB =40.161]]> 5.205 12.96% The area between AB <![CDATA[S BC =69.388]]> 9.906 14.28% The area between AB <![CDATA[S CD =65.662]]> 9.572 14.58% Areas outside D <![CDATA[S D =86.328]]> 12.457 14.43%

[0306] Table 2 Structural parameters of the positive electrode material precursors prepared in the examples and comparative examples

[0307]

[0308]

[0309] Test Example 2

[0310] Preparation of positive electrode materials for lithium-ion batteries:

[0311] The positive electrode material precursor prepared in the above example and LiOH are mixed uniformly in a molar ratio of 1:1.03 by a high-speed mixer to obtain a mixture;

[0312] The mixed material is sintered in a box furnace under air atmosphere (sintering temperature is 740° C., sintering time is 12 h), and the sintered material is cooled, crushed and sieved in sequence to obtain the positive electrode material for lithium-ion batteries.

[0313] Preparation of lithium-ion batteries:

[0314] (1) The above-mentioned lithium-ion battery positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) are mixed into a slurry at a ratio of 8:1:1, and the slurry is evenly coated on an aluminum foil with a length and width of 2 cm×1 cm to prepare a positive electrode sheet;

[0315] (2) Assemble the battery case, positive electrode sheet, negative electrode sheet (metal lithium sheet), diaphragm, spring, gasket and electrolyte into a button battery in a vacuum glove box.

[0316] The electrochemical performance of the prepared lithium-ion battery was tested using the Blue Electric test system CT3002A as follows:

[0317] ① Capacity test: The prepared button cell was charged at about 25°C at a constant current (C) of 0.1C until the voltage reached 4.2V, and then discharged at a constant current of 0.1C until the voltage reached 2.8V (first cycle), and the first coulombic efficiency was calculated (first coulombic efficiency % = 0.1C discharge capacity / 0.1C charge capacity);

[0318] ② Cycle performance test: The prepared button battery was subjected to different rate performance tests at about 25°C and in the voltage range of 2.8-4.2V. The battery was charged at a rate of 0.1C and discharged at a rate of 0.5C, and the 50-week cycle retention rate was calculated.

[0319] ③ Rate performance test: The prepared button batteries were subjected to different rate performance tests at about 25°C and in the voltage range of 2.8-4.2V. The charge rate was 0.1C, and the discharge rates were 0.1C, 0.2C, 0.5C, 0.8C, and 1C, respectively. The discharge capacity retention rate at 1C was calculated.

[0320] The above test results are shown in Tables 3 and 4.

[0321] Table 3 Capacity and cycle performance of lithium-ion batteries obtained from precursors of Examples 1-3 and Comparative Examples 1-3

[0322]

[0323] Table 4 Electrochemical performance results of lithium-ion batteries obtained from precursors of Examples 2 and 4-6

[0324]

[0325] It can be seen from the above results that the specific surface area of ​​the positive electrode material precursor provided by the present invention is small (5-10m 2 / g), which can reduce the sintering temperature required for the preparation of positive electrode materials and reduce the loss of discharge capacity; the high porosity (8-20%) of the secondary particles in the positive electrode material precursor can increase the contact area between the obtained positive electrode material and the electrolyte, increasing the Li + Transmission channel. The positive electrode material precursor provided by the present invention is applied to a lithium-ion battery, and the obtained lithium-ion battery has both high capacity and excellent cycle performance.

[0326] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cathode material precursor, characterized in that: The positive electrode material precursor comprises secondary particles composed of primary particles, wherein the porosity of the secondary particles is 8-20%; the specific surface area of ​​the positive electrode material precursor is 5-10m 2 / g.

2. The cathode material precursor according to claim 1, characterized in that: The pore uniformity coefficient R of the secondary particles 2 ≥0.

90.

3. The cathode material precursor according to claim 1, characterized in that: The average width of the primary particles on the surface of the positive electrode material precursor is 80-200 nm; And / or, the average aspect ratio of the primary particles on the surface of the positive electrode material precursor is (6-14): 1; And / or, the particle size D50 of the positive electrode material precursor is 16-20 μm, and can be 17-19 μm; And / or, the chemical formula of the positive electrode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.5≤x<1, 0.01≤y≤0.20, 0.05≤z≤0.30, 0≤v≤0.015, and M is selected from at least one of Al, Ti, Zr, Mo, W, B, Mg, Ba, Nb and Sr.

4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The positive electrode material precursor meets one or more of the following conditions: A. The porosity of the secondary particles is 13%-16%; B. The specific surface area of ​​the positive electrode material precursor is 6-8m 2 / g; C. Porosity uniformity coefficient R of the secondary particles 2 ≥0.95, optionally, the pore uniformity coefficient R of the secondary particles 2 ≥0.98; D. The chemical formula of the positive electrode material precursor is Ni x Co y Mn z M v (OH)2, wherein x+y+z+v=1, 0.8≤x<1, 0.03≤y≤0.10, 0.05≤z≤0.30, 0≤v≤0.015, and M is selected from at least one of Al, Ti, Zr, Mo, W, B, Mg, Ba, Nb and Sr.

5. A method for preparing a cathode material precursor according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: mixing a precipitant solution, a complexing agent solution and water to obtain a first base solution; Under the protection of inert gas, the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the first base liquid respectively and simultaneously to carry out a first coprecipitation reaction to obtain an intermediate; mixing the intermediate, the precipitant solution, the complexing agent solution and water to obtain a second base solution; The metal salt solution, the precipitant solution and the complexing agent solution are introduced into the second base solution simultaneously to carry out a second coprecipitation reaction, so as to obtain the positive electrode material precursor.

6. The preparation method according to claim 5, characterized in that: The preparation method meets one or more of the following conditions: (1) the pH value of the first base liquid is greater than the pH value of the second base liquid; (2) The temperature of the first coprecipitation reaction is less than the temperature of the second coprecipitation reaction; (3) controlling the flow rate of the precipitant solution so that the pH value of the first coprecipitation reaction sequentially experiences a first descending period, a first plateau period, a second descending period, and a second plateau period; (4) controlling the flow rate of the precipitant solution so that the second co-precipitation reaction includes a pH drop phase I and a pH plateau phase I; (5) The average particle size of the intermediate is 3.6-5.0 μm; (6) The sum of the molar concentrations of the metal elements in the metal salt solution is 1-3 mol / L; (7) The precipitant solution is a sodium hydroxide solution; (8) The complexing agent solution is an aqueous ammonia solution.

7. The preparation method according to claim 6, characterized in that: The preparation method meets one or more of the following conditions: a. The pH value of the first base liquid is 11.00-12.00, and the pH value of the second base liquid is 10.00-11.00; b. The temperature of the first coprecipitation reaction is 50-60°C, and the temperature of the second coprecipitation reaction is 65-80°C; c. the concentration of the complexing agent in the first base solution and the concentration of the complexing agent in the first coprecipitation reaction are each independently 3.0-5.0 g / L; d. the concentration of the complexing agent in the second base solution and the concentration of the complexing agent in the second coprecipitation reaction are each independently 3.0-5.0 g / L; e. the pH value of the first plateau in the first coprecipitation reaction is 10.50-11.00; f. The first coprecipitation reaction in the first plateau period is maintained for 6-10h; g. The pH value of the second plateau in the first coprecipitation reaction is 10.00-10.50; h. The second coprecipitation reaction further comprises a pH drop phase II, a pH plateau phase II, a pH drop phase III, a pH plateau phase III, and the pH value of the pH plateau phase III in the second coprecipitation reaction is 9.60-10.00; i. The pH value of the pH plateau phase I in the second coprecipitation reaction is 9.60-10.

00.

8. A positive electrode material for a lithium ion battery, characterized in that: The raw material of the lithium-ion battery positive electrode material includes the positive electrode material precursor according to any one of claims 1 to 5.

9. A lithium ion battery, characterized in that: Comprising the lithium-ion battery positive electrode material as claimed in claim 8.

10. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Positive electrode material precursor and preparation method thereof, positive electrode material and battery

    CN120637431A